2013
DOI: 10.5704/moj.1303.011
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Repair of Degenerative Tears of Tendo Achilles Using Peroneus Brevis Tendon: Early Results

Abstract: Reconstruction of degenerated ruptures of the tendoachilles is a challenge. Ruptured tendons and the remaining tendon ends are abnormal. A number of methods have been described in literature reconstruct the tendoachilles, but with variable results1. We used peroneus brevis tendon in 20 patients to augment the repair of degenerated tendoachilles tears by creating a dynamic loop as described by Teuffer et al2. All patients were followed up for atleast 18 months. At the last postoperative visit, 18 out of 20 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The modified RUPP Scores in this study showed statistically significant improvement from 3 months to 6 months and about 13 (59.1%) patients had excellent scores. This was comparable to those obtained in the study done byTawari et al where PB brevis was used, and they had about 50% patients had excellent scores(26).The mean total duration of surgery was 93.41 mins, out of which the mean time required to find, isolate and release MKH was noted to be 20.82 mins. So, the mean percentage of total duration of surgery was found to be 22.13%.…”
supporting
confidence: 88%
“…The modified RUPP Scores in this study showed statistically significant improvement from 3 months to 6 months and about 13 (59.1%) patients had excellent scores. This was comparable to those obtained in the study done byTawari et al where PB brevis was used, and they had about 50% patients had excellent scores(26).The mean total duration of surgery was 93.41 mins, out of which the mean time required to find, isolate and release MKH was noted to be 20.82 mins. So, the mean percentage of total duration of surgery was found to be 22.13%.…”
supporting
confidence: 88%
“…It should be noted that peroneus brevis tendon transfer results in most patients regaining their ability to engage in preinjury sports and daily activities [84]. The operated ankle may have lower peak torque and eversion strength compared to the unaffected limb, although such difference, though statistically significant, are of dubious clinical significance [85]. Maffulli et al [86] employed peroneus brevis tendon transfer to reconstruct the CATR with the defect of 4.0 to 6.5 cm in 16 patients.…”
Section: When Should Tendon Transfer Be Used?mentioning
confidence: 99%